Neurotoxic Agent-Induced Injury in Neurodegenerative Disease Model: Focus on Involvement of Glutamate Receptors - Jakaria, Md.; Park, Shin-Young; Haque, Md. Ezazul; Karthivashan, Govindarajan; Kim, In-Su; Ganesan, Palanivel; Choi, Dong-Kug (Frontiers in Molecular Neuroscience, 2018)
Glutamate receptors play a crucial role in the central nervous system and are implicated in different brain disorders. They play a significant role in the pathogenesis of neurodegenerative diseases (NDDs) such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Although many studies on NDDs have been conducted, their exact pathophysiological characteristics are still not fully understood. In in vivo and in vitro models of neurotoxic-induced NDDs, neurotoxic agents are used to induce several neuronal injuries for the purpose of correlating them with the pathological characteristics of NDDs. Moreover, therapeutic drugs might be discovered based on the studies employing these models. In NDD models, different neurotoxic agents, namely, kainic acid, domoic acid, glutamate, β-N-Methylamino-L-alanine, amyloid beta, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, 1-methyl-4-phenylpyridinium, rotenone, 3-Nitropropionic acid and methamphetamine can potently impair both ionotropic and metabotropic glutamate receptors, leading to the progression of toxicity. Many other neurotoxic agents mainly affect the functions of ionotropic glutamate receptors. We discuss particular neurotoxic agents that can act upon glutamate receptors so as to effectively mimic NDDs. The correlation of neurotoxic agent-induced disease characteristics with glutamate receptors would aid the discovery and development of therapeutic drugs for NDDs.